Ankylosing Spondylitis and Pregnancy: A Literature Review - Giovannopoulou, Eirini; Gkasdaris, Grigorios; Kapetanakis, Stylianos; Kontomanolis, Emmanuel (Current Rheumatology Reviews, 2017)
Background: Ankylosing Spondylitis (AS) is the prototype of a group of systemic rheumatic diseases collectively referred to as Spondylarthitides (SpA). It has now become clear that AS is not as rare as previously thought and, although it has an early onset in life affecting patients in their reproductive years, it has not been proved to adversely affect fertility in females. Objective: The aim of this review is to summarize all the recent data on AS and pregnancy in terms of fertility, disease course and pregnancy outcome from a clinical perspective. Method: A literature research was conducted based on the following medical databases: Pubmed/ Medline and the Cochrane Library. We searched for randomized controlled studies, casecontrol studies, cohort studies, patient and drug registers in relation to pregnancy and AS. Results: The existing data do not support a causal relationship between AS and infertility. The state of pregnancy is not associated with reduced disease activity in patients with AS. Additionally, AS tends to adversely affect health-related quality of life during pregnancy, in comparison with normal population and patients with rheumatoid arthritis. As far as the obstetrical outcome is concerned, there is no consensus on the significant association between AS and specific pregnancy, delivery and fetal complications. Conclusion: Previous studies are highly heterogenous and mainly retrospective and thus, the existing data are controversial and inconclusive. Subsequent studies are required to enlighten our knowledge on the interaction between AS and pregnancy.
Keywords: systemic rheumatic disease